Community attachment as a mediating variable in the relationship between residents’ perceived impact on sports tourism and support for the sector. - González García, Rómulo Jacobo; Gregori, Cristian; Martínez-Cevallos, Daniel; Pérez-Campos, Carlos; García-Pascual, Fernando (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The field of sports tourism is receiving increasing attention from various social actors, due to the important impact this economic sector has on various sectors of society. Once a locality becomes a tourist destination, the attachment of local residents will be affected by its development. Therefore, the aim of this study was to analyse residents’ perceptions of the impact of active-sport tourism, community attachment and support for the sector. The results of the study indicate that the higher the level of people’s positive perception of the social, cultural, environmental and economic impacts, the higher the support for tourism development. On the other hand, there is also a mediating influence of people’s attachment to the community between the relationship of perceived impacts and support for active-sport tourism development. These findings provide a better understanding of people’s perspectives for active-sport tourism, which can help guide future decisions regarding tourism practice, development and planning.